Silicon carbide MOSFETs in more electric aircraft power converters: the performance and reliability benefits over silicon IGBTs for a specified flight mission profile - O'Donnell, Shane; Debauche, Jean-Louis; Wheeler, Patrick; Castellazzi, Alberto (2016)
This paper describes the design, construction and performance of a 5 kVA aviation power module containing silicon carbide MOSFETs. The function and control of this module within a commercial aviation power electrical control unit (ECU) application is explained and the power dissipation benefits from the use of these MOSFETs instead of silicon IGBTs when driving an electrical motor controlling an aileron are presented. The paper shows the calculated reliability figures for the power module in this application and an application-specific reliability test to verify 150,000 flight hours of module operation is introduced. Performance test results from a prototype unit are also presented.